PENCIPTAAN SENDRATARI MALIN KUNDANG SANGGAR PINCUK BALEKAMBANG SOLO MELALUI PENDEKATAN KREATIVITAS - Efrida Efrida (Institut Seni Indonesia Surakarta, 2013)
Malin Kundang legend is very popular in Minangkabau community West Sumatra. Traditionalliterary work is very interesting and can be source for a creation of sendratari. This creation isstarted by reinterpreted the story of Malin Kundang. The interpretation is the priority for the sake ofperformance in order to make more prominent meaning. It is needed a theoretical approach inprocess of creation. The theory used in the creation is the theory of creativity in which include theproperty of authenticity (originality), fluency, elasticity or flexibility and elaboration the ability tocomplete the details or parts of concepts or understanding. The result of this study are 1) examinethe original story of Malin Kundang legend, 2) reinterpreted Malin Kundang legend , 3) create ascript to suit the mindset of spectators and crews, 4)selecting or creating dance that suit to thestory, 5) the process of work formation.